Kinetic and Thermodynamic Studies for Methylene Blue Adsorption using Activated Carbon Prepared from Agricultural and Municipal Solid Wastes - Abdullah Al-Othman, Zeid; Abdelaty Habila, Mohamed; Ali, Rahmat; Salah El-Din Hassouna, Mohamed (Asian Journal of Chemistry, 2013)
This study aimed to evaluate and optimize the removal of methylene blue onto low cost starting material activated carbon. The effects of pH, contact time, initial concentration on adsorption process were investigated. Results showed that effective adsorption was occurred in the pH range of 5-12. The maximum adsorption capacity (140.03 mg/g) was obtained at contact time 480 min, at initial methylene blue concentration of 150 ppm. Adsorption kinetics of methylene blue was analyzed by pseudo first order, pseudo second order and intraparticle diffusion models. Results showed that methylene blue adsorption onto activated carbon followed second order kinetics models most appropriately. Thermodynamic parameters; DGº, DHº and DSº indicate that the sorption process was spontaneous and endothermic in nature. The magnitude of DGº was -6.27 to -12 kJ/mol, the standard enthalpy and the entropy values in the range of 25-50 ºC were obtained as 44.13 kJ mol-1 and 158.3 kJ mol-1 K-1.